Potensi Terapeutik Ekstrak Purslane (Portulaca oleracea L.) dalam Pengelolaan Diabetes Tipe-2: Tinjauan Literatur - Arvilla Henarta Putri; Yennie Agnes Pranata (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterised by insulin resistance, aberrant insulin secretion, and persistent hyperglycemia. There are different treatments existing but there is a need for complementary. Portulaca oleracea L. (purslane) medicinal herb with bioactive substance having antidiabetic property. The purpose of this study was to aimed Portulaca oleracea L. therapeutic potential, bioactive components, and underlying processes in the treatment of type 2 diabetes. The literature review was developed through a comprehensive examination of published journal articles retrieved from major academic databases, including Google Scholar, NCBI, PubMed, and ScienceDirec. Many studies have demonstrated that Portulaca oleracea L. possesses significant antidiabetic effect. These seem to result from insulin-sensitizing,a generalized, suppression of NF-κB-related inflammation, AMPK pathway stimulation/activation of eNOS expression in general, gut bacteria regulation effects, and carbohydrate digesting inhibition; whether by glycemic index level processes use/alleviation of those responses as an energy expenditure process. The dose effective in animal studies is between 50 and 500 mg/kg/day. Immediate clinical trials (1.0–1.8 g/day) demonstrate powerful improvements of fasting glucose, HbA1c lipid metabolism, and oxidative stress marker. Portulaca oleracea L. showed promise as an additional treatment for type 2 diabetes. Its bioactive components work in concert to address a variety of pathogenic targets. To validate the best therapeutic use, standardized extraction procedures and extensive clinical dose-finding studies are required.